PREDIKSI FINANCIAL DISTRESS PADA KOPERASI SIMPAN PINJAM DI KABUPATEN BADUNG - Suhartiningsih, Ni Nyoman Tria; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This study aims to determine the effect on the financial ratios of financial distress and formed a discriminant model that capable of predicting financial distress in savings and credit cooperatives on Badung regency-Bali. This research was conducted at 32 savings and credit cooperatives and this research data is derived from secondary data. The research data was processed using discriminant analysis techniques. The results of the overall analysis of independent variables were tested showed there are three variables that influence financial distress. The three variable is RentAsset, MS/PDbBr, CR/PB. The discriminant model formed from the influential variables have 87.5% of predictive accuracy, so it can be said that the model is able to predict the financial distress in credit cooperatives on Badung regency-Bali.
Keywords: financial distress, savings and credit cooperatives, discriminant analysis